2021
DOI: 10.1007/s12088-021-00949-z
|View full text |Cite
|
Sign up to set email alerts
|

The Preventive Effects of Lactobacillus casei on Acute Lung Injury Induced by Lipopolysaccharide

Abstract: Lactobacillus has been reported to inhibit acute lung injury (ALI). However, the molecular mechanism of Lactobacillus casei ( L. casei ) in preventing ALI has not been identified, so we investigated whether L. casei pretreatment could inhibit the activation of TLR4/MyD88/NF-κB signaling pathway following ALI. ALI model was established by intraperitoneal injection of 2 mg/kg lipopolysaccharide (LPS) to female BALB/c mice. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Of the 49 included in vivo studies, 12 studies reported data from experiments performed using in vivo human model [ 45 , 50 60 ], 34 studies [ 29 , 32 , 36 41 , 43 , 61 – 85 ] used rodents (mice or rats), and the remaining three used sheep [ 44 ], cows [ 86 ] or pigs [ 42 ]. All included human studies (12 studies) used LPS administration with in vivo doses of 2–4 ng/kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 49 included in vivo studies, 12 studies reported data from experiments performed using in vivo human model [ 45 , 50 60 ], 34 studies [ 29 , 32 , 36 41 , 43 , 61 – 85 ] used rodents (mice or rats), and the remaining three used sheep [ 44 ], cows [ 86 ] or pigs [ 42 ]. All included human studies (12 studies) used LPS administration with in vivo doses of 2–4 ng/kg.…”
Section: Resultsmentioning
confidence: 99%
“… In one-challenge intervention, mice or rats were injected with or inhaled LPS [ 37 , 61 , 62 , 66 , 70 , 72 77 , 80 , 85 ], or were intranasally inoculated with S. pneumoniae [ 41 ], or intraperitoneally inoculated with E . coli [ 79 ], or underwent CLP [ 82 ].…”
Section: Supporting Informationmentioning
confidence: 99%
“…In this concern, new anti-inflammatory therapies as probiotics have deserved highlights due to beneficial effect on lung diseases, such as asthma, ARDS, COPD, and pneumonia [50][51][52][53]. Even in that preliminary, the present study shows that Lr restores the antiviral signaling and reduces Regarding the choice of the probiotic Lactobacillus rhamnosus (Lr) to carry out the experimental assays of the present study, this decision was made based on results published by our group that describe the beneficial effect of Lr on cell signaling of the lung inflammatory response and the airway remodeling observed in murine models of COPD and ARDS [54,55].…”
Section: Discussionmentioning
confidence: 99%